ChemInform Abstract: A Convenient Route to 1‐Alkyl‐5‐trifluoromethyl‐1, 2, 3‐triazole‐4‐carboxylic Acids Employing a Diazo Transfer Reaction. Issue 43 (7th October 2013) - Iminov, Rustam T.; Mashkov, Alexander V.; Chalyk, Bohdan A.; Mykhailiuk, Pavel K.; Tverdokhlebov, Anton V.; Tolmachev, Andrey A.; Volovenko, Yulian M.; Shishkin, Oleg V.; Shishkina, Svetlana V.
Abstract Application of this method is demonstrated in synthesis of Rufinamide‐derivative IV that was obtained in 4 steps and 73% overall yield.